Online pharmacies: desirable characteristics and regulations - Kumaran, Harshily; Long, Chiau Soon; Bakrin, Faizah Safina; Tan, Ching Siang; Goh, Khang Wen; Al-Worafi, Yaser Mohammed; Lee, Kah Seng; Lua, Pei Lin; Ming, Long Chiau (Springer Nature, 2020)
This commentary discusses desirable characteristics and regulations for online pharmacies. It highlights the growth of internet-based pharmacy services, consumer safety concerns, and the importance of clear regulatory and professional standards for online pharmaceutical services.